The effect of alkyl chain length on the structure of lead(ii) xanthates and their decomposition to PbS in melt reactions. Issue 41 (22nd September 2016) - McNaughter, Paul D.; Saah, Selina A.; Akhtar, Masood; Abdulwahab, Khadijat; Malik, M. Azad; Raftery, James; Awudza, Johannes A. M.; O'Brien, Paul
Abstract : Lead(ii ) n -alkylxanthates with varying alkyl groups are used in melt reactions to impart size control on the PbS nanocrystals formed. Abstract : A series of lead(ii ) alkylxanthates, [Pb(S2 COR)2 ] (R = ethyl (1 ), n -propyl (2 ), n -butyl (3 ), n -hexyl (4 ) or n -octyl (5 )) have been prepared and explored as single source precursors for use in melt reactions to form lead sulfide. X-ray single crystal structures of (2 ), (3 ) and (4 ) were used along with previously reported structures to investigate the influence of structure and chain length on the materials produced. The complexes were decomposed at 150, 175 or 200 °C forming PbS nanocrystals as confirmed by XRD and TEM. Analysis by SEM shows that the choice of precursor had an influence on nanocrystal size with longer alkyl chains resulting in smaller cubic nanocrystals. In addition to cubes, anisotropic growth was observed from decomposition of compound (5 ).